2010
DOI: 10.1161/circimaging.108.835793
|View full text |Cite
|
Sign up to set email alerts
|

Late Gadolinium-Enhancement Cardiac Magnetic Resonance Identifies Postinfarction Myocardial Fibrosis and the Border Zone at the Near Cellular Level in Ex Vivo Rat Heart

Abstract: Background— Using a resolution 1000-fold higher than prior studies, we studied (1) the degree to which late gadolinium-enhancement (LGE) cardiac magnetic resonance tracks fibrosis from chronic myocardial infarction and (2) the relationship between intermediate signal intensity and partial volume averaging at distinct “smooth” infarct borders versus disorganized mixtures of fibrosis and viable cardiomyocytes. Methods and Results— Sprague-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
2
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 40 publications
(42 reference statements)
11
125
2
1
Order By: Relevance
“…49 Late gadolinium enhancement imaging via cardiac magnetic resonance imaging is the gold standard method for the noninvasive evaluation of cardiac fibrosis. 50 Fibrosis severity detected via late gadolinium enhancement correlates significantly with STE-assessed strain parameters in patients with hypertrophic cardiomyopathy and Fabry disease. 19,20,23 However, in patients with higher-stage CKD and those with ESRD, gadolinium is contraindicated because of the risk of nephrogenic systemic fibrosis.…”
Section: Discussionmentioning
confidence: 94%
“…49 Late gadolinium enhancement imaging via cardiac magnetic resonance imaging is the gold standard method for the noninvasive evaluation of cardiac fibrosis. 50 Fibrosis severity detected via late gadolinium enhancement correlates significantly with STE-assessed strain parameters in patients with hypertrophic cardiomyopathy and Fabry disease. 19,20,23 However, in patients with higher-stage CKD and those with ESRD, gadolinium is contraindicated because of the risk of nephrogenic systemic fibrosis.…”
Section: Discussionmentioning
confidence: 94%
“…Schelbert et al 17 recently demonstrated the ability of highfield DHE-CMR to identify areas of fibrous tissue interspersed with viable myocardial cells in the periphery of infarct with image resolution of 50×51×51 μm. However, this study demonstrated that as image resolution decreased, more partial volume averaging occurred, resulting in overestimation of the PI area.…”
Section: Comparison Of Different Threshold Techniquesmentioning
confidence: 99%
“…In ex-vivo MRI, spatial resolution is close to the myocyte level, with a spatial resolution of 50×50×50 µm. 6 Often, only focal delayed enhancement can be identified, and detection of diffuse fibrosis is currently still limited. Be- cause often the fibrotic process is not as extensive as post-infarction scarring, but instead limited to increased collagenous tissue deposited around individual viable cells, the signal intensity is closer to that of normal tissue.…”
Section: Limitations Of Mrimentioning
confidence: 99%
“…Schelbert et al in their high-resolution ex-vivo animal study showed that areas of intermediate signal intensity corresponded to surviving muscle bundles within scar. 6 However, when they used retrospective degradation of the MR images to obtain a lower resolution comparable to that of clinical scans, areas of intermediate signal intensity were often due to volume averaging. Further animal experiments where postinfarction VTs were mapped demonstrated that with highresolution MRI, viable myofibers could be detected within the isthmus area of a post-infarction scar.…”
Section: Mri and Prior MImentioning
confidence: 99%